Thermal aging at 475 °C of newly developed lean duplex stainless steel 2404: Mechanical properties and corrosion behavior. (15th February 2017) - Silva, R.; Baroni, L.F.S.; Kugelmeier, C.L.; Silva, M.B.R.; Kuri, S.E.; Rovere, C.A.D.
Highlights: Influence of thermal aging at 475 °C on LDSS 2404 has been assessed. The presence of α′ phase decreases ferromagnetic behavior of the LDSS. An increase in hardness and drastic loss in absorbed energy of the LDSS was detected. The α' phase formation occurs by spinodal decomposition. The degradation of corrosion resistance is slower in LDSS 2404 than in DSS 2205. Abstract: An investigation was made of the effect of aging for up to 2000 h at 475 °C on the properties of the newly developed lean duplex stainless steel (LDSS) 2404. Due to its lower alloying content, the degradation of corrosion resistance as a function of thermal aging evolves more slowly in LDSS 2404 than in a standard duplex alloy (DSS 2205). The results also suggest that the mechanism of α' phase formation in the ferritic matrix occurs by spinodal decomposition and that this phenomenon has a stronger impact on the steel's mechanical properties than on its corrosion behavior.